Categorisation of Video Lecture Designs in Mooc for Technical and Vocational Education and Training Educators - Rahim, Muhamad Izzat; Shamsudin, Sarimah (Journal of Technical Education and Training, 2019)
Video lectures are the main content delivery mechanism in Massive Open Online Course (MOOC). It is used frequently in many MOOCs. This has resulted in the creation of many video lecture designs. Scholars agree that noticing the design is significant for both educators and learners. Thus, this study aims to investigate the designs of Malaysian Technical and Vocational Education and Training (TVET) video lectures in MOOC. Using video lectures (N=15) collected from MOOC in TVET discipline, analysis was done by comparing the video lectures with Crook and Schofield’s video lecture design taxonomy. It was found that Malaysian TVET video lectures can be categorized into six different designs. Voice over slides was the most frequent design used. From the six designs, three new ones were found from the video lectures. Hence, the findings of this study may be beneficial for both TVET educators and students when engaging with video lectures.